Implementación de un módulo didáctico de fluido hidráulico para la visualización y análisis de pérdida por fricción en tuberías en el Laboratorio de Ingeniería Electromecánica de la Universidad Técnica de Cotopaxi periodo 2017 - Analuisa Tonato, Edwin Armando (2017)
The practical test bench, performs an analysis to check load losses in pipes and fittings, is part of a system of equipment necessary to carry out practices within the training of the Electromechanical Engineer especially in the field of fluid mechanics. In the laboratory of Electromechanical Engineering has not developed a didactic module with which it is possible to carry out practices, analysis and verification of losses by friction that exists in pipes and accessories, it is here where the idea of implementing this didactic module is born. The disadvantage in the subject of fluids is that it is theoretical, without the possibility of checking and visualizing the data obtained physically from exercises proposed by the teacher. The purpose of the implementation of this didactic module is to identify, analyze, visualize and calculate friction losses in pipes and fittings. This will be done using fittings for connections and piping directions in the same way the use of Pitot and Venturi tubes that are the most used when proposing application exercises.